(untitled) (Castilla. Estudios de Literatura, 2012)
There are a few books written by José Jiménez Lozano among these, Maestro Huidobro is considered to be a short story or “fable”. All of them share the singularity of its pervaded symbolic characteristic. In this essay after a critique/review reading related to the chapter “La casa” by Maestro Huidobro based on literary analysis of the Poetry of Imagination. The house, as his own private space is vital to understand the character’s imagination in José Jiménez Lozano’s short stories.